Ответы и объяснения

  • 1asasas
  • почетный грамотей
2014-02-11T16:49:52+00:00
3в^2-3с^2.            3(в^2-с^2).          Сокращаем крест накрест(в-с).       3(в-с).        3(в-с)
------------     =                          =              остается                                  =                   =                 =    
(в-с)(3в+3).           (в-с)(3в+3).                                                                          (3в+3с).       3(в+1)


       Сокращаем 3.           в-с
=                                  =    
                                                в+1